TOOLKIT FOR MODERNIZATION OF PUBLIC POLICY IN THE SPHERE OF DEVELOPMENT OF PRIVATE HEALTHCARE INSTITUTIONS - VASYLTSIV, Taras; BILETSKA, Iryna; RUDKOVSKA, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In the study, attention is updated to the problem of stimulating the development of private business in the field of health care. The purpose of the study is to develop a toolkit for modernization of public policy in the field of development of private health care institutions. It has been established that the health care system is naturally considered as a prerequisite and an integral component of the sustainable development of society, and the modern trends that determine the priorities of state policy in this area are determined by such leading goals of the country’s socio-economic progress as sustainability of economic growth, social safety and improvement of the population’s well-being, strengthening of human potential, improvement of the quality of medical care and overcoming the demographic crisis. It is shown that today, in the conditions of existing challenges to the functioning and development of domestic medicine, the task of improving the public policy of stimulating the development of private health care institutions in Ukraine, providing medical and related services, especially on a systemic basis, has become critically relevant. The directions (vectors) of improving the public policy of stimulating the development of private health care institutions have been determined, namely: (1) improvement of regulatory and legal regulation; (2) improvement of financial and resource support; (3) improvement of the business environment. The applied value of the research results lies in the identification of obstacles to the development of small private health care institutions in Ukraine. The scientific novelty of the research results lies in the substantiation of the system of tools for stimulating the development of private health care institutions.